The Effect of Physical Activity on Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus in Masbagek District, East Lombok - Cahyadi Pratama; Mei Ling Zhang (Media of Health Research, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or resistance. Physical activity has been widely recognized as a non-pharmacological strategy to control blood glucose. However, limited evidence exists regarding its effectiveness in rural Indonesian populations. This study aims to evaluate the effect of physical activity on blood glucose levels in patients with T2DM in Masbagek District, East Lombok. A quasi-experimental study with a pre–post test design was conducted from January to April 2024. A total of 80 participants diagnosed with T2DM were recruited using purposive sampling. The intervention group (n=40) performed moderate-intensity physical activity (30 minutes of brisk walking, 5 days/week) for 12 weeks, while the control group (n=40) continued routine care. Fasting blood glucose levels were measured before and after the intervention. Data were analyzed using paired and independent t-tests. The intervention group showed a significant reduction in mean fasting blood glucose from 178.5 ± 22.4 mg/dL to 142.3 ± 18.9 mg/dL (p < 0.001), whereas the control group showed no significant change (176.8 ± 20.1 mg/dL to 173.2 ± 21.4 mg/dL, p = 0.214). Regular moderate-intensity physical activity significantly reduced blood glucose levels in T2DM patients in Masbagek District. These findings emphasize the importance of integrating structured physical activity into community-based diabetes management programs in rural areas.